Labor productivities and labor costs in Euroland - Horst Siebert (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1998)
The paper presents labor productivities in the member countries of Euroland. The result is that there is quite a divergence in labor productivities (per head) in the European Monetary Union. The Netherlands and Italy reach 85 percent of the West German level, Spain 62 and Portugal 35. This implies that labor costs have to be differentiated substantially between the euro countries. Labor costs relative to the West German level are also calculated. The paper analyzes the implication of diverging labor productivities for wage policy and for the financing of the social security systems in the European Monetary Union.
Keywords: J24; H55; F15; F36; 330; Arbeitsproduktivität; Lohnstückkosten; Vergleich; Europäische Wirtschafts- und Währungsunion; EU-Staaten